Distribution and periodicity of sandflies (Diptera: Phlebotominae) along different altitudes in Asir Region, Southwest of Saudi Arabia - M.A. Kenawy; H.A. Al Ashry; M. Shobrak (Journal of Entomological and Acarological Research, 2015)
Asir Region in the southwest of Saudi Arabia has been a subject for expansion of agricultural projects, urbanization, which presumably have impact on distribution of phlebotomine sandflies. Few reports are available on sandflies in this region which is an important focus of cutaneous leishmaniasis. Therefore, this study aimed at updating the species composition, distribution and periodical fluctuation of sandflies in this region. Specimens were monthly collected by the Center for Disease Control light traps for one year in four localities representing different altitudes. In five other, collections were twice during the year period. Ten species (six Phlebotomus and four Sergentomyia) were identified, of which P. arabicus (32%) was the most common followed by P. bergeroti (29%) and P. sergenti (15%). Of the reported species, S. palestinensis is considered a new record from Asir. Sandflies were more common and maximum biodiversity was observed in lowlands and not in high altitudes. At different altitudes, the two commonest species were more active during spring. Sandfly density (sandfly/trap) was directly related to temperature and inversely related to altitude, relative humidity (RH) and wind velocity (P<0.05). To sum up, the distribution and abundance of sandflies in Asir are influenced by a combination of different factors: temperature, RH, wind velocity and altitude.